Castration‐resistant prostate cancer diagnosed during leuprorelin treatment for spinal and bulbar muscular atrophy. Issue 4 (10th April 2022) - Yanase, Atsuhi; Sugihara, Toru; Akimoto, Takahiro; Yokoyama, Hirotaka; Kamei, Jun; Fujisaki, Akira; Ando, Satoshi; Naoi, Tameto; Morita, Mitsuya; Fujimura, Tetsuya
Abstract : Introduction: We report a prostate cancer case diagnosed during leuprorelin treatment for spinal and bulbar muscular atrophy which is a X‐linked recessive, lower motor neuron disease. Case presentation: A 64‐year‐old man who had received leuprorelin treatment over 3 years for his spinal and bulbar muscular atrophy presented with an enlarged prostate accompanied by abdominal pain and constipation. An abnormally high serum prostate‐specific antigen of 17.7 ng/mL and a low (castration level) serum testosterone level of 0.23 ng/mL were measured. Prostate needle biopsy revealed adenocarcinoma of the prostate. Orchiectomy, darolutamide, and radiation therapy for the prostate were initiated, resulting in a favorable response which was maintained at 12 months of treatment. Conclusion: Prostate cancer can occur even when leuprorelin is used for spinal and bulbar muscular atrophy; therefore, checking serum prostate‐specific antigen to screen for prostate cancer before leuprorelin administration should be considered.